Correlation of Medical Treatment for Wound Infection with Isolated Bacteria and Antibiotics Sensitivity Profile in Baqubah Teaching Hospital - A Mohammed, Ammar; A Al-karkhi , Mohamed; A Al-Taie, Firas; Ahmed Lateef , Imad (Diyala Journal of Medicine, 2020)
Background: Despite of the advancement in surgery, surgical techniques and use of antibiotics prophylaxis, postoperative infections remain the commonest postoperative complications and one of the most frequently encountered nosocomial infections worldwide. These infections lead to increase morbidity with the attendant increase in cost of therapy. Objective: To evaluate the antimicrobial susceptibility pattern among the most common bacteria associated with postoperative wound infections. Patients and Methods: (126) swab specimens were cultured and isolates were identified by gram stain ,morphological and cultural characteristics of the colonies. The standard disc diffusion methods were done for determination of Antibiotics Resistance of all isolates as described by the Clinical Laboratory Standard Institute (CLSI)16. Results: A total of (126) patients presented with infected wounds were enrolled in this study. Out of (126) patients studied (43)patient(34%) had no growth. While the others (83) patient (66%) had positive bacterial isolate. From those with positive isolates (47) patient(57%) were male and 36 (43%) were female.The common bacterial isolate were E.coli (29%) then Staphylococcus aureus and Acinetobacter spp.(19%).Sensitivity testing show that E.coli had high resistance to Piperacillin, Aztreonam, Ticarcillin and Sulfamethoxazole. And Staphylococcus aureus had high resistance to Erythromycin and Sulfamethoxazole. Conclusion: The common pathogen was E.coli and it was resistant to the commonly used antibiotics. While Staph.aureus was still sensitive to many antibiotics.